USE OF ATHEROGENIC INDICES AS ASSESSMENT METHODS FOR CLINICAL ATHEROSCLEROTIC DISEASES - Souza , Cristiana Daniela de; Oliveira , Jim Davis de; Junqueira , Julia Ferreira; Obeid , Gabriel Raizama; Andrade , Luana Lopes; Pitanga , Anthony Yuri Viana; Queiros , Admilson Barbosa; Boaventura , Isadora Bueno Moraes; Ribeiro , Bruna Martins; Gomes , Charles Correa; Nascimento , Lara Hiorrana de Souza; Barbosa, Karen Cristtine Araujo (Brazilian Journal of Implantology and Health Sciences, 2024)
Accurate assessment of clinical atherosclerotic diseases is essential to guide effective therapeutic interventions, and atherogenic indices have emerged as valuable methods in this setting. The complexity of these pathologies demands approaches that go beyond the simple measurement of total cholesterol, requiring tools that consider the interaction between different lipoproteins and other risk factors. In this context, the use of atherogenic indices appears as a promising approach, providing a more comprehensive and refined assessment of atherosclerotic conditions. Objective: To comprehensively analyze scientific studies published in the last 10 years that investigated the use of atherogenic indices as methods of evaluating clinical atherosclerotic diseases. The review seeks to consolidate the available evidence by examining the effectiveness of these indices in early identification, risk stratification and monitoring the progress of atherosclerotic diseases. Methodology: The systematic review was conducted following the PRISMA guidelines. The PubMed, Scielo and Web of Science databases were consulted to identify relevant studies published in the last 10 years. The descriptors used were "atherogenic indices", "atherosclerotic diseases", "clinical assessment", "lipoproteins" and "cardiovascular risk factors". Inclusion criteria considered original studies that investigated the use of atherogenic indices in clinical populations, while exclusion criteria involved studies with unrepresentative samples and inadequate atherosclerotic assessment methods. Results: The results of the review highlight the diversity of available atherogenic indices and their usefulness in evaluating different aspects of atherosclerotic diseases, including prediction of cardiovascular events, risk stratification and treatment monitoring. The analysis identified indices that proved to be particularly sensitive and specific in different clinical contexts. Conclusion: In summary, the systematic review highlights the relevance of atherogenic indices as valuable tools in the assessment of clinical atherosclerotic diseases. The diversity of these indices and their ability to provide comprehensive information highlights their importance in clinical practice, contributing to a more refined and personalized approach to the management of these conditions.